The effects of economic shift on town growth :a case of Marudi townland - Kiu, Sok Ping (Universiti Malaysia Sarawak, (UNIMAS), 2001)
The aim of this study is to explore the consequences of a economic decline on a town growth. The case area is Marudi Townland a town located in the Fourth Division and is accessible only by river and air. A total of 55 households were sampled randomly, several timber-related companies, several non-timber related businesses, and major public agencies were interviewed.